Assessment of Mechanical Properties of Corroded Reinforcement in Chloride Environment Based on Corrosion Rate Monitoring - Grandić, Davor; Grandić, Ivana Štimac; Šćulac, Paulo (Salehan Institute of Higher Education, 2024)
Existing models for the evaluation of mechanical properties of corroded reinforcement, defined as a function of the mean cross-sectional loss or mass loss of the reinforcement, are not suitable in the case of chloride-induced corrosion, which causes irregular corrosion attack with pronounced localized damage—pits, whose geometry and spacing have a major influence on the mechanical properties of the reinforcement. Models that consider the irregularity of damage due to chloride corrosion are efficient, but as with models based on cross-sectional or mass loss, it is necessary to extract corroded rebars from the reinforced-concrete structure, which is a destructive procedure that can only be performed to a limited extent on an in-service building. To fill the above gaps, a new method based on the non-destructive measurement of corrosion parameters is proposed. The corrosion depth determined from the monitoring correlates directly with the remaining mechanical properties of the reinforcement; therefore, it is not necessary to determine the remaining cross-sectional area and geometry of the pits. The proposed models are based on experimental research on reinforced-concrete beam specimens subjected simultaneously to sustained loading and accelerated chloride corrosion in an environmental chamber in order to induce corrosion similar to that on real structures. Doi: 10.28991/CEJ-2024-010-11-02 Full Text: PDF